Evaluation of factors associated with fear and anxiety in the orthodontic treatment of adult patients - Serrat Lacasta, Lucía; de la Cruz Vigo, Susana; Leonelli, Manuele (Medicina Oral, 2025)
Background: Despite the technological advances made in dentistry, anxiety and fear of pain due to dental treatment are still common. Most patients in a dental clinic suffer some symptoms of anxiety, which can appear at different times. The objective is to know the degree of anxiety and the factors associated with this anxiety during orthodontic treatment. Material and Methods: 180 adult patients who started orthodontic treatment were selected and a questionnaire was administered at the beginning and after six months of treatment. The SDAI anxiety scale was used to determine the degree of anxiety and its own questionnaire to determine its relationship with the different factors of orthodontic treatment. Results: When performing descriptive and inferential statistics, it is obtained that 72% of patients at the beginning of orthodontic treatment present a certain degree of anxiety. Through individual logistic regression using anxiety as a response and each of the demographic variables at six months as predictors, it is obtained that gender(OR=3.15) and occupation(OR=3.11) are the two significant predictors (P<0, 05). Using Fisher’s exact test of independence, the additional questions are related to the demographic variables and anxiety, obtaining a value of P<0.05 in 27(of 114) non-independent relationships between the additional questions and the demographic/anxiety variables. Conclusions: 38%of patients who begin orthodontic treatment have high anxiety, but after 6 months this anxiety drops to 22%. Women and patients with active work are the most likely to present more anxiety at 6 months. The biggest concerns at the beginning of treatment are: Changes in appearance(Q15),Eating(Q18),Appliance loss(Q19),Hygiene(Q24),Tooth loss(Q25),Extend treatment(Q26),Expectations(Q27) and Retention(Q28).Of these eight, only three continue to worry patients after six months: appliances loss(Q19),Hygiene(Q24) and Tooth Loss(Q25).At the beginning of treatment there are two questions that do not worry: Enter alone(Q10) and take medications(Q21).Four more are added after six months: Embarrassment(Q16),Getting used to it(Q17),Periodic visits(Q22) and Emergencies(Q23).
Keywords: SDAI scale; Dental anxiety; Adults; Orthodontic treatment; 32 Ciencias Médicas; ODS 3 - Salud y bienestar